Association of transforming growth factor (TGF) p1 T(861-20)C polymorphism with bone mineral density and TGFip gene expression in postmenopausal osteoporosis - Elena Vasilyevna Chetina; M Yu Krylov; N V Demin; O A Nikitinskaya; E A Korotkova; N V Toroptsova; K A Maslova; L I Benevolenskaya; V A Myakotkin (Научно-практическая ревматология)
Objective: to study the mechanism for the involvement of ТGFβ1 T(861-20)C in bone resorption in postmenopausal osteoporosis (OP). Material and methods. DNA from 158 postmenopausal women and patients with OP and from 89 healthy age-matched women was examined by polymerase chain reaction (PCR)-restriction fragment length polymorphism (PCR-RFLP) analysis. Bone mineral density (BMD) was estimated by dual-energy X-ray absorptiometry. Standard biochemical protocols were used to detect alkaline phosphatase activity and calcium and phosphorus levels in serum. Total RNA was isolated from the peripheral blood of 32 patients with OP and 39 healthy donors and used for real-time PCR study. Results. No significant differences were found in the frequency of individual alleles and genotypes between the OP group and control donors. The minor T allele frequency was 0.27. There was a significant correlation of ТGFβ1 T(861-20)C polymorphism with low lumbar spine BMD (r=0.18; p=0.025) in Russian patients with OP. Age-adjusted (Z-score) BMD in CC genotype carriers turned to be significantly lower than that in CT and TT genotype carriers. This was accompanied by lower ТGFβ1 gene expression in the peripheral blood of CC genotype carriers (n=10) as compared to the combined group of carriers of two other genotypes (n=22) in the OP group (p=0.03). No changes in ТGFβ1 gene expression were seen in healthy women who were CC genotype carriers (n=18) as compared to the combined representatives of two other genotypes (n=21). Overall, the OP group exhibited significantly lower ТGFβ1 gene expression than the healthy controls (p=0.04). Conclusion. The association of ТGFβ1 (861-20)CC genotype with lower lumbar spine BMD in patients with OP is attended by decreased ТGFβ1 gene expression. Therefore, ТGFβ1 T(861-20)C polymorphism may be a predictor for the development of OP and the more severe form of the disease may be expected in (861-20)CC genotype carriers.